PERANCANGAN SISTEM E-COMMERCE BERBASIS WEB DENGAN BARCODE SCANNER UNTUK PENGELOLAAN DATA PRODUK - Eka Bagus; Santoso, Agustinus Budi Santoso; Iman Saufik Suasana (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2026)
This study aims to design and develop a web-based e-commerce system integrated with a barcode scanner to support product data management at Toko Keko Branded Yogyakarta. The system is proposed as a solution to the previous manual ordering and recording processes, which were time-consuming and prone to errors. The application was developed using PHP and MySQL, with Bootstrap to provide a responsive user interface. The integration of a barcode scanner enables faster and more accurate product input, stock updates, and product search without manual typing. The development process follows the Waterfall model, including requirements analysis, system design, implementation, testing, and maintenance. The results show that the system improves the efficiency of product management, facilitates transactions, and supports the digitalization of store operations.